Process for preparing few-layer molybdenum diselenide nano-film at low temperature and application

The preparation of a small layer of molybdenum diselenide nanofilm under mild conditions through low-temperature chemical vapor deposition technology solves the problems of complex processes and high growth temperature in the existing methods, and achieves high uniformity and simplicity of operation, which significantly improves its performance in many fields.

CN119800321AActive Publication Date: 2025-04-11XIANGTAN UNIV +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510297358.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-13
Publication Date
2025-04-11
Estimated Expiration
2045-03-13

AI Technical Summary

Technical Problem

The existing preparation methods for the small-layer molybdenum diselenide nano films have problems such as complex process, difficulty in layer regulation, limited grain growth and excessive growth temperature, which are difficult to meet the needs of industrial production.

Method used

Low-temperature chemical vapor deposition technology (CVD) is adopted to achieve precise layer control, large-area continuous growth and uniform film formation through the synergistic effect of precursor molecular structure optimization and spatial domain growth control strategy. The process is carried out under mild conditions, which significantly reduces the growth temperature.

Benefits of technology

It has achieved high uniformity, simplicity of operation, process stability and cost-effective advantages, significantly improving the controllability and repeatability of material synthesis. The prepared two-dimensional MoSe2 film has excellent performance in the fields of photoelectronic detectors, gas sensing elements and electrocatalytic hydrogen evolution reactions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119800321A_ABST
    Figure CN119800321A_ABST
Patent Text Reader

Abstract

The invention discloses a process for preparing a molybdenum diselenide nano-film at a low temperature and application of the molybdenum diselenide nano-film. According to the method, an accurate selenium-molybdenum source concentration regulation and control system is constructed, and the structural optimization design of a molybdenum source precursor is combined, so that the preparation of the few-layer molybdenum diselenide nano-film with controllable layer number and high crystallization quality is realized. The method comprises the following specific steps: firstly, heating molybdenum foil to a certain temperature in a tubular furnace, then introducing deionized water to synthesize molybdenum oxide foil in a water vapor microenvironment, and then by taking the obtained molybdenum oxide foil and selenium powder as precursors, preparing the molybdenum oxide foil by regulating and controlling the gradient field of the sublimation temperature of the selenium powder and the temperature of a substrate and the concentration of a selenium-molybdenum source. And the large-area few-layer molybdenum diselenide nano-film is obtained. Experimental results show that the method has the advantages of being low in growth temperature, high in synthesis efficiency, controllable in layer number and the like, and in an electrochemical hydrogen evolution test, few-layer molybdenum diselenide shows the performance obviously superior to that of a single-layer structure. A new strategy is provided for large-scale preparation of the two-dimensional transition metal chalcogenide, and the method is suitable for industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of chalcogenide film and photoelectric detector preparation, and specifically relates to a process and application of low-temperature preparation of a few-layer molybdenum diselenide nanofilm. Background Art

[0002] Transition metal chalcogenides (TMDs) are an important class of two-dimensional materials, expressed as MX2 type, where M is a transition metal element (such as tungsten, molybdenum, etc.) and X is a chalcogen element (such as selenium, tellurium, sulfur, etc.). This type of compound has shown broad application potential in optoelectronics, electronics, catalysis and energy conversion due to its adjustable band gap, high specific surface area, high carrier mobility, high on-off ratio and unique photo / electrocatalytic activity. Among many TMDs, molybdenum diselenide (MoSe2) has attracted much attention due to its narrow band gap (about 1.5 eV, lower than 1.9 eV of molybdenum disulfide), high active site density, narrow linewidth and excellent photoelectric properties. Especially in the field of electrochemical catalytic hydrogen evolution, the grain boundaries of few-layer MoSe2 nanofilms are rich in active sites, which significantly improves its catalytic performance and enables it to perform excellent performance in the electrochemical hydrogen evolution reaction.

[0003] At present, researchers are exploring precise preparation methods for few-layer MoSe nanofilms. Existing synthesis techniques mainly include hydrothermal method, mechanical exfoliation and high-temperature selenization treatment (mechanical spin coating of molybdenum source precursor first). Although these methods have made some progress, they still have limitations. For example, hydrothermal method and mechanical exfoliation perform poorly in terms of layer number control and sample uniformity, and it is difficult to meet the needs of industrial production. The high-temperature selenization method has a complicated process and small grain size due to its growth temperature usually higher than 700 °C, which limits its application in a wider range of fields.

[0004] Therefore, it is extremely important to explore a method for preparing a few-layer MoSe nanofilm that can achieve large-area preparation, simple process, low cost and low synthesis temperature. In addition, a highly uniform nanofilm structure is crucial to achieving stable electrochemical performance, which will significantly improve the efficiency and stability of energy conversion technologies such as electrocatalytic hydrogen evolution. By optimizing the preparation process, the number of MoSe nanofilm layers can be precisely controlled, thereby optimizing its physical and chemical properties. This innovative preparation method will not only help promote the application of MoSe nanofilms in the industrial field, but will also provide strong support for the development of related technologies. Summary of the invention

[0005] In view of the problems of complicated process, difficult layer control, limited grain growth and too high growth temperature in the preparation of few-layer MoSe2 nanofilms by mechanical exfoliation, high-temperature selenization, hydrothermal method and other methods in the above-mentioned existing processes, the present invention provides a process and application for preparing few-layer MoSe2 nanofilms at low temperature. The process is based on the principle of chemical vapor deposition technology (CVD). Through the synergistic effect of precursor molecular structure optimization and spatial confined growth control strategy, the number of layers of two-dimensional MoSe2 nanofilms is precisely controlled, large-area continuous growth and uniform film formation are achieved under mild conditions, which not only achieves high uniformity, but also significantly reduces the growth temperature. The experimental results show that the process has the advantages of simple operation, process stability and cost-effectiveness, and significantly improves the controllability and repeatability of material synthesis. In particular, the prepared two-dimensional MoSe2 film shows excellent performance in the fields of photoelectron detectors, gas sensor elements and electrocatalytic hydrogen evolution reaction, verifying its broad application prospects.

[0006] The technical solution adopted by the present invention to achieve the above-mentioned purpose is as follows: The process for preparing a few-layer MoSe nanofilm at low temperature comprises the following steps: S1. Push the metal molybdenum foil to the center of the hot zone of the tube furnace, raise the temperature to 465 ~ 500 ℃, move the quartz boat loaded with deionized water to a position 4 ~ 5 cm away from the molybdenum foil, and perform an oxidation reaction in an air atmosphere for 8 ~ 15 min to obtain water-assisted synthesized oxidized molybdenum foil; S2. The molybdenum oxide foil synthesized by water-assisted synthesis is transferred to the top of the growth substrate, and is pushed back to the center of the hot zone of the tube furnace. A quartz boat loaded with selenium powder is placed upstream of the tube furnace in the direction of carrier gas flow; S3. The reaction chamber is purged with argon gas for cleaning. In a H2 / Ar mixed atmosphere, the temperature in the center of the hot zone of the tube furnace is raised to 450-800°C by program temperature increase and maintained for 8-20 min for growth. S4. After terminating the heating, the mixed gas is kept flowing, and the tube furnace is naturally cooled to room temperature (20-25°C), and then the tube furnace is opened to obtain a few-layer MoSe nanofilm.

[0007] Preferably, in step S1, a metal molybdenum foil with a purity of 4N grade (99.99%) is used, and its thickness is controlled to be 2 to 5 μm; a small amount of deionized water is added by loading it into a quartz boat and limiting it to a position 4 to 5 cm away from the molybdenum foil to construct a local water vapor microenvironment. The inventor unexpectedly discovered during the experiment that this design can induce the amorphous transformation of molybdenum oxide in the oxidation reaction stage of air atmosphere (8-15min, 465-500°C), thereby significantly reducing the crystallinity of the formed molybdenum oxide foil. This structural characteristic significantly promotes the layer-limited growth mechanism of the subsequent MoSe2 nanostructure, so that the generated MoSe2 nanofilm mainly appears in the morphology of a few layers.

[0008] Preferably, in step S2, the selenium powder is 4N grade purity selenium powder (Se, 99.99%), and its dosage range is controlled in the range of 50-300 mg. In the chemical vapor deposition process, the loading amount of the high-purity selenium source directly affects the saturated vapor pressure of the gas-phase Se species, thereby regulating the layered growth kinetics of the two-dimensional MoSe2.

[0009] Preferably, in step S2, the growth substrate is soda-lime glass (SiO2-CaO-Na2O), silicon (Si) or sapphire (α-Al2O3). Experiments have confirmed that the surface and interface characteristics of the substrate are one of the decisive factors for the growth of the two-dimensional MoSe2 layered structure, and are crucial to controlling the growth of MoSe2 nanofilms in a few-layer morphology. Through lattice matching and surface energy regulation mechanisms, the preferred substrate can effectively suppress the three-dimensional island growth mode and realize the synthesis of two-dimensional materials with a few-layer configuration with controllable thickness.

[0010] Preferably, in step S2, the confinement height between the water-assisted synthesized molybdenum oxide foil and the growth substrate is 1 to 5 mm. The design of the confinement height can effectively regulate the precursor vapor concentration gradient, suppress the three-dimensional island growth mode, and promote the two-dimensional layer-by-layer assembly process dominated by interlayer van der Waals forces.

[0011] Preferably, in step S2, the upstream of the tube furnace is 21 to 24 cm from the center of the hot zone of the tube furnace. The optimized configuration of this parameter can ensure the directional transmission of the precursor vapor under the action of the carrier gas (H2 / Ar), while avoiding the nucleation runaway phenomenon caused by premature thermal decomposition. Experimental verification shows that the 21-24 cm axial spacing design can maintain the selenium vapor partial pressure in the optimal process window of 0.1-0.5 Torr, effectively balancing the surface diffusion and chemical adsorption kinetics.

[0012] Preferably, in step S3, when the reaction chamber is purged, the argon flow rate used for purging is set at 300-500 sccm, and the purging time is 30-60 minutes. When performing the reaction chamber cleaning operation, it is of great significance to appropriately increase the argon flow rate. Its advantage is that it can fully improve the cleaning efficiency, thereby achieving comprehensive and detailed cleaning results, ensuring that the cleaning work is thoroughly completed and meeting the process requirements.

[0013] Preferably, in step S3, the programmed temperature control time is 25 to 35 min.

[0014] Preferably, in step S3, in the H2 / Ar mixed atmosphere, the H2 flow rate is 3 to 7 sccm, and the Ar flow rate is 65 to 150 sccm. Experimental verification shows that precise control of the hydrogen ratio can optimize the crystal growth kinetics process. At the same time, reasonable adjustment of the argon flow rate has multiple technical advantages. It can maintain the chemical inertness of the reaction system by establishing a stable fluid mechanics boundary layer, avoid the plasma activating effect caused by excessive flow velocity gradient, and realize the economical utilization of gas resources.

[0015] The few-layer MoSe2 nanofilm obtained by the above process can be used in gas sensor elements, photoelectron detectors or electrocatalytic hydrogen evolution reactions, and can show excellent performance and has broad application prospects.

[0016] Compared with the existing process, the beneficial effects of this technical solution are as follows: The present invention uses an innovative precursor preparation scheme to introduce deionized water as a medium during the oxidation stage of molybdenum foil, thereby achieving significant regulation of the orderliness of the crystal structure of the oxidized molybdenum foil (XRD spectrum shows that the grain size is reduced by about 40%). This treatment method successfully induces the formation of a layered MoO(OH)2 dielectric phase and constructs a nucleation kinetic environment suitable for the growth of few-layer MoSe2 nanofilms, thereby creating favorable conditions for the controllable preparation of large-area few-layer MoSe2 nanofilms at low temperatures, making the preparation process more efficient and controllable.

[0017] (2) The present invention adopts a self-catalytic conversion mechanism, and no external catalyst is required in the whole process. Under the premise of ensuring the reaction activity, the metal residue problem caused by the traditional catalytic system is eliminated, the process flow is simplified, and the production cost is significantly saved.

[0018] (3) The present invention adopts atmospheric pressure chemical vapor deposition (CVD) technology. Compared with the hydrothermal method, mechanical stripping method and high-temperature selenization process after molybdenum source pre-coating, the present invention can synthesize large-area continuous, layer-controlled and highly uniform molybdenum diselenide nanofilms, and through precise feedback control of the selenium / molybdenum molar ratio, the number of layers of the molybdenum diselenide nanofilms can be precisely controlled. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 The digital photos of the molybdenum oxide foil synthesized without water assistance and with water assistance in Example 1; Figure 2 The Raman spectra of the molybdenum oxide foil synthesized without water and with water in Example 1 are characterized; Figure 3 This is a Raman spectrum characterization diagram of the molybdenum oxide foil synthesized with water in Example 1; Figure 4 This is an X-ray diffraction characterization diagram of the molybdenum oxide foil synthesized with water in Example 1; Figure 5 This is an X-ray diffraction characterization diagram of the molybdenum oxide foil synthesized without water assistance in Example 1; Figure 6 This is an optical microscope characterization image of molybdenum diselenide obtained in Example 2; Figure 7 This is a characterization diagram of the Raman spectrum of molybdenum diselenide obtained in Example 2; Figure 8 This is an optical microscope characterization image of molybdenum diselenide obtained in Example 3; Fig. 9 This is a scanning electron microscope characterization image of molybdenum diselenide obtained in Example 3; Fig.10 This is an atomic force microscope characterization image of molybdenum diselenide obtained in Example 3; Fig.11 This is a characterization diagram of the Raman spectrum of molybdenum diselenide obtained in Example 3; Fig.12 This is a characterization diagram of the photoluminescence of molybdenum diselenide obtained in Example 3; Fig.13 The X-ray energy spectrum characterization diagram of the Mo 3d orbital and the Se 3d orbital of the molybdenum diselenide obtained in Example 3; Fig.14 The low-magnification transmission electron microscope (a) and high-magnification transmission electron microscope characterization images (b) of the molybdenum diselenide obtained in Example 3; Fig.15 This is an optical microscope characterization image of the large-area single-layer molybdenum diselenide nanofilm (the mass of selenium powder is 100 mg) obtained in Example 4; Fig.16 This is an optical microscope characterization image of the large-area single / double mixed-layer MoSe nanofilm (mass of selenium powder is 150 mg) obtained in Example 4; Fig.17 This is an optical microscope characterization image of the large-area double-layer molybdenum diselenide nanofilm (the mass of selenium powder is 200 mg) obtained in Example 4; Fig.18This is an optical microscope characterization image of the large-area few-layer molybdenum diselenide nanofilm (the mass of selenium powder is 250 mg) obtained in Example 4; Fig.19 This is an optical microscope characterization image of the large-area single-layer MoSe nanofilm (the oxidation temperature of the Mo foil is 465° C.) obtained in Example 4; Fig. 20 This is an optical microscope characterization image of the large-area single / double mixed layer MoSe nanofilm (the oxidation temperature of the Mo foil is 475° C.) obtained in Example 4; Fig.21 This is an optical microscope characterization image of the large-area double-layer MoSe nanofilm (the oxidation temperature of the Mo foil is 485° C.) obtained in Example 4; Fig. 22 This is an optical microscope characterization image of the large-area few-layer MoSe nanofilm (the oxidation temperature of the Mo foil is 495° C.) obtained in Example 4; Fig.23 This is an optical microscope characterization image of the single-layer molybdenum diselenide nanosheet obtained in Example 5; Fig.24 This is an atomic force microscope characterization image of the single-layer molybdenum diselenide nanosheet obtained in Example 5; Fig.25 These are the electrochemical performance test results of the single-layer molybdenum diselenide nanosheet and the large-area few-layer molybdenum diselenide nanofilm in Example 6. DETAILED DESCRIPTION

[0020] The technical solution of the present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. However, it should be noted that the protection scope of the present invention is not limited to the following embodiments. Example 1

[0021] The metal molybdenum foil was placed in the center of the hot zone of the tubular furnace and heated to 475°C at a rate of 19°C / min using a programmed temperature method. Then a quartz boat filled with 1.5 ml of deionized water was pushed to a position 5 cm away from the molybdenum foil and oxidized in an air atmosphere. After 10 min, the heat source was turned off and the furnace was allowed to cool naturally to room temperature to obtain water-assisted synthesized oxidized molybdenum foil.

[0022] Through macroscopic morphology comparison analysis (such as Figure 1 As shown in Figure 2, there are significant differences between the molybdenum oxide foils synthesized without water assistance and those synthesized with water assistance. Raman spectroscopy test (as shown in Figure 2 Figures 2 to 3 ) shows: MoO2 foil synthesized with water has a peak at 889.8 cm -1There is an obvious characteristic peak at the point, which corresponds to the formation characteristics of the MoO(OH)2 phase, indicating that under high-temperature oxidation, the molybdenum foil reacts with water molecules to form MoO(OH)2. Compared with the molybdenum oxide foil synthesized without water assistance, the intensity of the Raman characteristic peak of the molybdenum oxide foil synthesized with water assistance is significantly weakened, and the main peak is slightly shifted at a low frequency. In addition, the half-width (FWHM) of the Raman characteristic peak of the molybdenum oxide foil synthesized with water assistance becomes wider, indicating that the lattice defect density is significantly increased.

[0023] In order to further reveal the effect of deionized water treatment on the structure of molybdenum oxide foil, X-ray diffraction (XRD) technology was used for phase analysis (e.g. Figures 4 to 5 ). The results show that the diffraction peak intensity of the molybdenum oxide foil synthesized with water at 31.7° (corresponding to the MoO3 (110) crystal plane) is significantly lower than that of the molybdenum oxide foil synthesized without water, which proves that its crystal order is significantly reduced. In addition, the present invention also found a more obvious diffraction peak of MoO(OH)2, which once again proves that the hydrothermal process successfully induced the formation of molybdenum oxyhydroxide intermediate (MoO(OH)2). Example 2

[0024] Substrate pretreatment: A 1.0 mm thick soda-lime glass substrate (size 0.7 cm×2 cm) was selected and placed on the graphite sheet surface. The water-assisted synthesized molybdenum oxide foil was cut into a rectangular sheet of 2 cm×1.5 cm and folded in half along the width direction to form a microstructure with an edge height of 2.0±0.1 mm, so that the confinement height between the molybdenum oxide foil and the glass substrate was 1.0 mm.

[0025] Thin film deposition system assembly: Push the molybdenum oxide foil and the glass substrate together into the center of the hot zone of the tube furnace. Load 275 mg of selenium powder into a quartz boat and place it 18.5 cm upstream of the center of the hot zone according to the direction of the gas flow. After sealing the chamber, pretreatment was performed: argon gas was introduced into the reaction chamber at a flow rate of 512 sccm for 5 min, and then switched to a hydrogen-argon mixed gas (H2: 6 sccm, Ar: 65 sccm) and continued to purge for 2 min to stabilize the gas environment in the tube furnace.

[0026] Chemical Vapor Deposition Process: A two-stage heating program was used: in the initial stage, the temperature was raised to 450 °C at a rate of 15 °C / min (taking 25 min), and the temperature was maintained for 12 min of growth reaction. After the reaction was completed, it was naturally cooled to room temperature to obtain the target product, and the soda-lime glass substrate with MoSe growth was taken out for analysis.

[0027] Observation by optical microscopy (OM) Figure 6) It can be seen that the MoSe2 film prepared by water-assisted synthesis of molybdenum oxide foil presents a typical few-layer nanostructure with uniform lateral size distribution. Figure 7 The Raman spectrum also shows that a few-layer structure with low defect density was successfully constructed. Example 3

[0028] On the basis of maintaining the substrate treatment process of Example 1, the heat treatment parameters were adjusted: the heating zone of the tube furnace was heated to 750°C in 25 minutes, and the loading position of the quartz boat was adjusted to the upstream area 22.5 cm from the heating center. The other process parameters (gas flow rate, pretreatment time, etc.) were maintained as set in Example 1. After the reaction was completed, it was naturally cooled to room temperature to obtain the target product. The morphology of the molybdenum diselenide film prepared in Example 3 is as follows Figure 8 As shown. Figure 8 It can be seen that the molybdenum diselenide film grown using water-assisted synthesized molybdenum oxide foil as a precursor presents a typical few-layer nanostructure.

[0029] Fig. 9 Scanning electron microscopy (SEM) showed that the film was uniformly distributed in islands; Fig.10 Atomic force microscopy (AFM) reveals the monolayer and bilayer structures, with significant surface morphology fluctuations (obvious wrinkles) in the bilayer region. Fig.11 The Raman spectrum characterization diagram shows that, compared with the literature data, the A 1g The characteristic peak positions all red-shifted. This phenomenon is mainly due to the presence of a certain number of selenium vacancies inside the sample and the strain caused by thermal mismatch between the material and the substrate during the cooling process. 2g 1 The peak is consistent with the literature data, further confirming that the grown sample is a few-layer MoSe2 nanofilm structure.

[0030] from Fig.12 From the photoluminescence characterization diagram, it can be observed that the band gap of the single-layer MoSe2 nanofilm shows a significant characteristic peak at 808 nm due to its direct band gap characteristics. In contrast, the double-layer and triple-layer MoSe2 nanofilms have lower intensity of characteristic peaks because their band gaps are indirect band gaps, which leads to quenching during photon transitions.

[0031] Fig.13 The X-ray energy spectrum characterization diagram further confirmed the chemical composition of the few-layer MoSe2 nanofilm structure. In the Mo3d diagram, two characteristic peaks can be observed, corresponding to Mo 3d 5 / 2 and Mo 3d 3 / 2 , and their binding energies are 228.53 eV and 231.58 eV, respectively. Similarly, in the Se 3d spectrum, two characteristic peaks are observed, corresponding to Se 3d 5 / 2 and Se3d3 / 2 , and their binding energies are 54.69 eV and 55.68 eV, respectively. The positions of these characteristic peaks are consistent with the data in previous literature. The calculated Mo / Se atomic ratio is 1 / 1.71, which indicates that there are many selenium vacancies in the obtained sample.

[0032] Fig.14 The transmission electron microscopy (TEM) characterization results of few-layer MoSe nanofilms are shown. Fig.14 It can be observed in a that the few-layer MoSe nanofilm presents a typical layered structure, and its edge part shows obvious atomic layer stacking characteristics. This layered structure is a typical feature of MoSe, indicating that the sample has a good crystal structure and a small number of layers.

[0033] exist Fig.14 In b, the high-resolution transmission electron microscopy image further reveals the atomic arrangement of the few-layer MoSe nanofilm. It can be seen that the atomic arrangement presents a highly ordered hexagonal lattice structure, which is consistent with the crystal structure of MoSe. The spacing between each atomic layer is about 0.615 nm, which is consistent with the theoretical interlayer spacing of MoSe, further confirming the high quality and few-layer characteristics of the sample.

[0034] In addition, no obvious defects or impurities were observed in the transmission electron microscopy images, indicating that the prepared few-layer MoSe nanofilm has high purity and crystallinity. Such high-quality few-layer MoSe nanofilms have important application prospects in optoelectronic devices and catalysis. Example 4

[0035] Based on the growth process of Example 2, by adjusting the concentration of selenium and the oxidation temperature of the molybdenum foil (using a water-assisted method), the number of layers of the MoSe2 nanofilm was successfully controlled, and other experimental conditions remained unchanged. The characterization results are as follows: Fig.15 As shown in Figure 22. The research results show that the number of layers of molybdenum diselenide changes with the concentration of selenium powder and the oxidation temperature of molybdenum foil. When the selenium concentration and the oxidation temperature of molybdenum foil are low, the molybdenum diselenide sample is mainly composed of a single-layer nanofilm. As the selenium powder concentration and the oxidation temperature of the molybdenum foil increase, the sample gradually changes from a single layer to a double layer. Finally, when the selenium powder concentration and the oxidation temperature of the molybdenum foil are too high, the molybdenum diselenide is mainly composed of three layers and a few layers. In addition, the research of the present invention also found that more double-layer and triple-layer molybdenum diselenide nucleates from the grain boundaries and grows inward. This is mainly attributed to the fact that during the growth process, the defects at the grain boundaries make the energy required for the nucleation of molybdenum diselenide at the grain boundaries lower, thereby making it easier to induce the growth of molybdenum diselenide at the grain boundaries. Example 5

[0036] Based on the growth process of Example 3, other experimental conditions remain unchanged. When the molybdenum oxide foil synthesized without water is used as a precursor, the grown molybdenum diselenide is mainly a single-layer nanosheet, and its optical microscope characterization is as follows: Fig.23 In addition, Fig.24 The atomic force microscopy characterization results also further confirmed the successful preparation of single-layer MoSe nanosheets. Example 6

[0037] The electrochemical hydrogen evolution performance of single-layer MoSe2 nanosheets and few-layer MoSe2 nanofilms was tested. Fig.25 As shown in Figure 1, in a saturated KCl solution, the electrochemical hydrogen evolution reaction was carried out with AgCl as the reference electrode. From the linear sweep voltammetric characteristic curve (LSV) in Figure a, it can be seen that when the current is 10 mA / cm 2 When the starting potential is lower, the few-layer MoSe2 nanofilm has a lower starting potential than the single-layer MoSe2 nanosheet. Figure b and Figure c show the Tafel slope and impedance of the few-layer MoSe2 and single-layer MoSe2, respectively. The few-layer MoSe2 nanofilm shows a lower Tafel slope and impedance than the single-layer MoSe2 nanosheet, which indicates that the few-layer MoSe2 nanofilm has better catalytic performance. Figure d is the linear sweep voltammetric characteristic curve of the few-layer MoSe2 nanofilm after 5000 cycles. It can be seen from the figure that the sample still has excellent catalytic performance after 5000 cycles, and at 10 mA / Cm 2 There was no obvious increase in the starting potential during the current flow, indicating that the sample has high stability.

Claims

1. A process for preparing a few-layer MoSe nanofilm at low temperature, characterized in that: The steps include: S1. Push the metal molybdenum foil to the center of the hot zone of the tube furnace, raise the temperature to 465 ~ 500 ℃, move the quartz boat loaded with deionized water to a position 4 ~ 5 cm away from the molybdenum foil, and perform an oxidation reaction in an air atmosphere for 8 ~ 15 min to obtain water-assisted synthesized oxidized molybdenum foil; S2. The molybdenum oxide foil synthesized by water-assisted synthesis is transferred to the top of the growth substrate, and is pushed back to the center of the hot zone of the tube furnace. A quartz boat loaded with selenium powder is placed upstream of the tube furnace in the direction of carrier gas flow; S3. The reaction chamber is purged with argon gas for cleaning. In a H2 / Ar mixed atmosphere, the temperature in the center of the hot zone of the tube furnace is raised to 450-800°C by program temperature increase and maintained for 8-20 min for growth. S4. After terminating the heating, the mixed gas is kept flowing, and the tube furnace is naturally cooled to room temperature (20-25°C), and then the tube furnace is opened to obtain a few-layer MoSe nanofilm.

2. The process for preparing a few-layer MoSe2 nanofilm at low temperature according to claim 1, characterized in that: In step S1, a metal molybdenum foil with a purity of 4N grade is used, and its thickness is controlled to be 2 to 5 μm.

3. The process for preparing a few-layer MoSe nanofilm at low temperature according to claim 1, characterized in that: In step S2, the selenium powder is 4N grade purity selenium powder, and its usage range is controlled in the range of 50-300 mg.

4. The process for preparing a few-layer MoSe2 nanofilm at low temperature according to claim 1, characterized in that: In step S2, the growth substrate is one of soda-lime glass, sapphire or silicon.

5. The process for preparing a few-layer MoSe2 nanofilm at low temperature according to claim 1, characterized in that: In step S2, the confinement height between the water-assisted synthesized molybdenum oxide foil and the growth substrate is 1 to 5 mm. The design of the confinement height can effectively regulate the precursor vapor concentration gradient, suppress the three-dimensional island growth mode, and promote the two-dimensional layer-by-layer assembly process dominated by interlayer van der Waals forces.

6. The process for preparing a few-layer MoSe2 nanofilm at low temperature according to claim 1, characterized in that: In step S2, the upstream of the tube furnace is a position 21 to 24 cm away from the center of the hot zone of the tube furnace.

7. The process for preparing a few-layer MoSe2 nanofilm at low temperature according to claim 1, characterized in that: In step S3, the argon gas flow rate used for purging is set at 300-500 sccm, and the purging time is 30-60 minutes.

8. The process for preparing a few-layer MoSe2 nanofilm at low temperature according to claim 1, characterized in that: In step S3, the programmed temperature control time is 25 to 35 minutes.

9. The process for preparing a few-layer MoSe2 nanofilm at low temperature according to claim 1, characterized in that: In step S3, in the H2 / Ar mixed atmosphere, the H2 flow rate is 3 to 7 sccm, and the Ar flow rate is 65 to 150 sccm.

10. Use of the few-layer MoSe2 nanofilm obtained by the process according to any one of claims 1 to 9 in gas sensor elements, photoelectron detectors or electrocatalytic hydrogen evolution reactions.

Citation Information

Patent Citations

  • Spiral WS2 layered two-dimensional nano material with layer-by-layer twisting angle and preparation method thereof

    CN118441261A

  • Process for synthesis of monolayer transition metal dichalocogenide

    IN202221005450A

  • AEROSOL-ASSISTED CHEMICAL VAPOR DEPOSITION METHOD AND NiVOx MATERIAL FOR ELECTROCHEMICAL WATER OXIDATION

    US20240044026A1